ANALISIS POSISI DAN TINGKAT KETERGANTUNGAN IMPOR GULA KRISTAL PUTIH DAN GULA KRISTAL RAFINASI INDONESIA DI PASAR INTERNASIONAL - Handini Pujitiasih; Bustanul Arifin; Suriaty Situmorang (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
This research aims to analyze the Indonesian sugar trading position in international trade and level of Indonesia's dependence on imported sugar. The analysis method used in this research was analysis of Indonesian sugar trade positions using the Agricultural Specialization Index, and analysis dependence on sugar imports using the Import Dependency Ratio. The results showed that: (1) sugar of Indonesia has weak competitiveness because the value of Indonesian sugar trade specialization index was under one (<1). This indicated that Indonesia is a net importer of the sugar commodity, sugar that can be directly consumed or sugar is used as raw material for the food and beverage industry (2) Indonesian sugar import dependency rate that was calculated by Import Dependency Ratio indicated the extent of dependency on Indonesian imported sugar.Keywords: refined sugar, import dependence, white sugar